Perceived weight discrimination, changes in health, and daily stressors. Issue 10 (1st September 2016) - Sutin, Angelina R.; Stephan, Yannick; Grzywacz, Joseph G.; Robinson, Eric; Daly, Michael; Terracciano, Antonio
Abstract : Objective: To examine whether perceived weight discrimination is associated with change in health markers over time and whether it is associated with daily stressors, physical symptoms, and affect. Methods: Participants were selected from the Midlife in the United States (MIDUS) study if they had data on perceived weight discrimination and health markers at MIDUS II (2004–2006), health markers at MIDUS III (2013–2014), and a body mass index ≥25 kg/m 2 ( N = 1, 841). A subset of these participants ( N = 1, 153) reported on their experiences daily for 8 days as part of the second National Study of Daily Experiences. Results: Perceived weight discrimination was associated with declines in mental and physical health over time (median β = 0.06). Participants who reported weight discrimination experienced more daily stressors ( β = 0.13), physical symptoms ( β = 0.13), and negative affect ( β = 0.13) and less positive affect ( β = −0.12) over the 8 days of the second National Study of Daily Experiences. Weight discrimination was most strongly associated with interpersonal stressors (median β = 0.14), feelings of anger ( β = 0.16) and frustration ( β = 0.14), lower attention ( β = −0.14) and activity ( β = −0.16), and more nonspecific physical symptoms (e.g., fatigue; β = 0.10). Conclusions: This research replicates the association between perceived weight discrimination and worse health over time and extends this literature to show that people who experience weight discrimination have more daily stressors, physical symptoms, and negative emotions.